Methotrexate reduces HbA1c concentration but does not produce chronic accumulation of ZMP in patients with rheumatoid or psoriatic arthritis. (2nd September 2016) - Perdan-Pirkmajer, K; Pirkmajer, S; Thevis, M; Thomas, A; Praprotnik, S; Hočevar, A; Rotar, Ž; Gašperšič, N; Sodin-Šemrl, S; Žibert, J; Omersel, J; Chibalin, AV; et al.
Abstract : Objectives : The mechanism by which methotrexate (MTX) improves glucose homeostasis in patients with rheumatoid (RA) and psoriatic arthritis (PsA) remains undetermined. Animal studies indicate a role for intracellular accumulation of 5-aminoimidazole-4-carboxamide-1-β-d -ribofuranosyl 5ʹ-monophosphate (ZMP) but this has not been directly demonstrated in humans. We explored whether accumulation of ZMP is associated with improvements in glucose homeostasis during MTX therapy. Method : MTX-naïve, non-diabetic RA (n = 16) and PsA (n = 10) patients received uninterrupted MTX treatment for 6 months. To evaluate whether ZMP accumulated during MTX therapy, we measured the concentration of ZMP in erythrocytes and the concentration of its dephosphorylated derivative 5-aminoimidazole-4-carboxamide-1-β-d -ribofuranoside (AICAR) in urine using liquid chromatography mass spectrometry (LC-MS/MS). To assess glucose homeostasis, we determined the concentration of glycated haemoglobin (HbA1c) and homeostasis model assessment of insulin resistance [HOMA-IR: fasting glucose (mmol/L) × fasting insulin (μU/mL)/22.5]. Results : Erythrocyte ZMP and urinary AICAR concentrations did not increase during 6 months of MTX therapy. HbA1c concentration was reduced from 5.80 ± 0.29% at baseline to 5.51 ± 0.32% at 6 months (p < 0.001), while HOMA-IR remained unaltered. Reduction in HbA1c concentration was not associated with increased ZMP or AICAR concentrations. Conclusions : MTX therapy probably does not produce a chronic increase in erythrocyte ZMP or urinary AICAR concentrations. Collectively, our data do not support the hypothesis that MTX improves glucose homeostasis through chronic accumulation of ZMP.